Revisão taxonômica de Rhaebo guttatus (Schneider, 1799) (Anura: Bufonidae) - Ribeiro, Maurivan Vaz (2019)
This work deals with the taxonomy of Rhaebo guttatus, a bufonid toad widely distributed in South America. We used both traditional (morphology and morphometry) and modern methodologies (molecular and niche overlap) in order to elucidate the complex taxonomy of the species and define its taxonomic status in Brazil. We first conducted phylogenetic analyses of R. guttatus populations that occur within the Brazilian territory. In addition, we assessed 1040 specimens from museum collections. We obtained a total of 20 morphometric variables in order to investigate whether there was a differentiation among population from different watersheds. Phylogenetic analysis revealed populations from Tocantins-Araguaia (TA) watershed is a subclade of the populations from the Amazon basin (AM). We identified three genetic clusters which were spatially coherent with AM, TA and a contact zone between southern AM and TA. Individuals from AM populations are larger than individuals from TA basin. We found low niche overlap with temperature seasonality and precipitation influencing AM populations and temperature strongly influencing TA population. Sexual dimorphism is also present in R. guttatus. In conclusion, we redescribed R. guttatus based on the holotype but including Brazilian specimens.